2013
DOI: 10.1016/j.ntt.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dietary-exposure to non-coplanar PCBs induces behavioral disruptions in adult zebrafish and their offspring

Abstract: The use of polychlorinated biphenyls (PCBs) has been banned for several decades. PCBs have a long biological half-life and high liposolubility which leads to their bioaccumulation and biomagnification through food chains over a wide range of trophic levels. Exposure can lead to changes in animal physiology and behavior and has been demonstrated in both experimental and field analyses. There are also potential risks to high trophic level predators, including humans. A maternal transfer has been demonstrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 92 publications
0
24
1
Order By: Relevance
“…Only a few studies have examined the impact of organic pollutant on the fish PMR. Using a similar approach, Péan et al (2013) reported a stimulation of this PMR following PCB contamination transferred to offspring zebrafish larvae. Furthermore, changes in zebrafish swimming rates, depending on PBDE congeners, have been shown by Usenko et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have examined the impact of organic pollutant on the fish PMR. Using a similar approach, Péan et al (2013) reported a stimulation of this PMR following PCB contamination transferred to offspring zebrafish larvae. Furthermore, changes in zebrafish swimming rates, depending on PBDE congeners, have been shown by Usenko et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Results were expressed as a percentage of all surviving larvae. response Behavioral tests were conducted to monitor photomotor response (PMR) following the procedure described by Péan et al (2013) with slight modifications. The day before analysis, 4-dpf larvae were acclimated individually in a 24-well plate (Krystal 24, transparent bottom, and opaque walls) with 2 mL of E3 medium in a climate chamber (28±0.5°C; 14-h light/10-h dark photoperiod).…”
Section: Zebrafish Embryo-larval Assaysmentioning
confidence: 99%
“…Furthermore, testing for behavioral endpoints in zebrafish can be performed from as early as the larval stages shortly after hatching, through the juvenile and adult stages, enabling accurate timing of phenotype occurrence and persistence. Although most of the zebrafish studies on the long-term effects of developmental chemical exposure have focused on adult behavior (Lee and Freeman, 2014b, Levin et al, 2003, Levin et al, 2011), a few investigators have taken advantage of the zebrafish model to look at neurobehavioral effects over multiple life-stages (Eddins et al, 2010, Pean et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Continuous exposure to A1254 from immediately after fertilization until testing at 7dpf has also been found to disrupt performance on an optomotor assay consistent with impaired visual acuity (Zhang et al, 2015). Finally, offspring of adult zebrafish that had been exposed to a PCB mixture of 13 congeners for 8 months were found to be hyperactive at 5 dpf (Péan et al, 2013). …”
Section: Introductionmentioning
confidence: 99%